EFEKTIFTAS MEDIA SOLAR SYSTEM SCOPE DALAM MENINGKATKAN PEMAHAMAN SISWA TERHADAP MATERI TATA SURYA - Khatimah, Ismi Aryanti Khusnul; Fatkhomi, Fahmi; Atika, Nur; Taowatto, Sutita (Universitas Negeri Medan, 2023)
Learning media is one of the ways or tools used in the learning process. This is done with the aim of facilitating learning activities, as well as in order to support the success of the teaching and learning process. Therefore, this research was conducted with the aim of knowing the effectiveness of using solar system scope media in increasing students' understanding of solar system material in one of the schools located in Satun-South Thailand. This research is a qualitative research, while the data collection uses observation, interview, and evaluation methods. In this study also used a questionnaire on students' understanding of the solar system material using the solar system scope application. Based on the research that has been done, the results show that by utilizing the solar system scope application, learning on solar system material can be said to be effective, and of course it can make it easier for students to understand existing solar system material.